Beyond bulk: Density fractions explain heterogeneity in global soil carbon abundance and persistence. (16th December 2021) - Heckman, Katherine; Hicks Pries, Caitlin E.; Lawrence, Corey R.; Rasmussen, Craig; Crow, Susan E.; Hoyt, Alison M.; von Fromm, Sophie F.; Shi, Zheng; Stoner, Shane; McGrath, Casey; Beem‐Miller, Jeffrey; Berhe, Asmeret Asefaw; et al.
Abstract: Understanding the controls on the amount and persistence of soil organic carbon (C) is essential for predicting its sensitivity to global change. The response may depend on whether C is unprotected, isolated within aggregates, or protected from decomposition by mineral associations. Here, we present a global synthesis of the relative influence of environmental factors on soil organic C partitioning among pools, abundance in each pool (mg C g −1 soil), and persistence (as approximated by radiocarbon abundance) in relatively unprotected particulate and protected mineral‐bound pools. We show that C within particulate and mineral‐associated pools consistently differed from one another in degree of persistence and relationship to environmental factors. Soil depth was the best predictor of C abundance and persistence, though it accounted for more variance in persistence. Persistence of all C pools decreased with increasing mean annual temperature (MAT) throughout the soil profile, whereas persistence increased with increasing wetness index (MAP/PET) in subsurface soils (30–176 cm). The relationship of C abundance (mg C g −1 soil) to climate varied among pools and with depth. Mineral‐associated C in surface soils (<30 cm) increased more strongly with increasing wetness index than the free particulate C, but both pools showed attenuated responses to the wetness index at depth. Overall, these relationships suggest a strong influence of climate on soil C properties, and a potential loss of soil C from protected pools in areas with decreasing wetness. Relative persistence and abundance of C pools varied significantly among land cover types and soil parent material lithologies. This variability in each pool's relationship to environmental factors suggests that not all soil organic C is equally vulnerable to global change. Therefore, projections of future soil organic C based on patterns and responses of bulk soil organic C may be misleading. Abstract : In the first global meta‐analysis to examine both radiocarbon and C concentrations among different soil C pools, we found that three critical carbon pools (free particulate, occluded particulate, and mineral associated) respond differently to climate. Moisture had an almost equal influence as temperature on C persistence and abundance, highlighting the need for climate change studies focused on moisture manipulations. The strong variation in pool characteristics and their relationship to environmental factors indicates that we need to go beyond bulk soil carbon measurements to understand and model the responses of soil organic carbon to global change; it is critical to evaluate distinct pools as response variables.